Interconnection between IP Networks and Wireless Sensor Networks - Brandon Keith Maharrey; Alvin S. Lim; Song Gao (International Journal of Distributed Sensor Networks)
With applications ranging from environmental and health monitoring to military surveillance and inventory tracking, wireless sensor networks (WSNs) are changing the way we collect and use data and will be a major part of our technological future. The decreased manufacturing cost of these small devices has made it reasonable to deploy many sensor nodes—tens to thousands and more—over large and small indoor and outdoor areas for sensing tasks. With this increase in density data-gathering problems come. It would be useful if an IP-based host could collect information from multiple remote data-centric networks via transparent communication among sensor nodes and IP-based hosts, using a common application programming interface (API). Two APIs are presented for efficiently producing data in WSN and retrieving the data from an IP network. An associated WSN middleware layer called dynamic service is used to effectively interconnect these two APIs. These three components work together in harmony to enable IP-based hosts to gather sensed data from one or more remote WSNs through application-layer gateways which provide seamless interconnection between different remote WSNs and the IP network.